Iatrogenic Paradoxical Stroke in a Patient With Catheter-Associated Thrombosis and Systemic-to-Pulmonary Venous Shunt - Lucas J. Policastro MD; Kristaq Koci DO (SAGE Publishing, 2018)
Paradoxical embolism occurs when thrombotic material traverses a right-to-left shunt. We describe the first case of paradoxical stroke resulting from manipulation of a disused chemotherapy port. Contrast studies revealed that the mechanism was systemic-to-pulmonary venous shunt, in which systemic veins drain into the left atrium via collaterals. Chronically thrombosed central venous catheters may result in venous stenosis and shunt formation, exposing patients to risks of paradoxical stroke, acute coronary syndrome, hypoxemia, and other complications. This case highlights the life-threatening complications that may result from neglect of an implantable central venous catheter. Preventative measures are to promptly recognize and treat catheter-related thrombosis and to remove unneeded catheters.